ANALISIS PENYIMPANAN BIOMASSA KARBON PADA LAHAN HUTAN SEKUNDER DAN PERTANIAN DI KECAMATAN LEMBAH SEULAWAH KABUPATEN ACEH BESAR - Rosmalia Rosmalia (Jurnal Real Riset, 2021)
This research aims to know the ability of biomass carbon storage above and below ground level in the system of forestry and agriculture to know the changes in biomass carbon that results from changes in land use, forest with an area of 1020 ha research object. This research was carried out during 3 (three) months. This research method using destructive sampling technique system of quadrants. The observed variables are C-organic carbon stored in soils and different types of land use. The analysis of samples carried out in the laboratory analysis of Soil Faculty of Agriculture University of Syiah Kuala Balai and laboratory study of agricultural technology, Banda Aceh. The results showed that the number of the largest carbon reserve in the followed forestry of 241,36 ton/ha, and agriculture 6,62 ton ha, The magnitude of the carbon deposits and deposits of soil organic matter on a farm is affected by high population. Keywords : Biomass carbon, soil organic-C, forestry , agriculture Valley of Seulawah